Exposure to local violent crime and childhood obesity and fitness: Evidence from New York City public school students. (November 2022) - Laurito, Agustina; Schwartz, Amy Ellen; Elbel, Brian
Abstract: This paper estimates the relationship between neighborhood violent crime and child and adolescent weight and fitness. It uses detailed data from the Fitnessgram assessments of public school students in New York City matched to point specific crime data geocoded to students' residential location. Our empirical approach compares the weight and fitness outcomes of students exposed to a violent crime on their residential H-block with those living in the same census tract but not exposed to violent crime in close proximity to their home. We find for adolescent girls, increases in BMI that range from 0.01 to 0.035 standard deviations and an increase in the probability of overweight of 0.5 to 1.7 percentage points. We find little evidence that BMI, obesity, and overweight change as a result of violent crime for adolescent boys, and younger children. Results are not explained by declines in physical fitness. Highlights: Exposure to local violent crime increases the BMI and probability of overweight of adolescents girls (14 to 18 years old). The BMI of adolescent girls exposed to more than 20 crimes is 7.5 percent higher relative to the mean for their group. They also experience a 5.5 percent increase in the probability of overweight relative to their group mean. We find no change in physical fitness due to neighborhood violence, with few exceptions among boys 9 to 13 years of age. We find no evidence that property crime affects weight or fitness outcomes.